2000
DOI: 10.1177/109114210002800604
|View full text |Cite
|
Sign up to set email alerts
|

Valued-Added Tax Revenues in Mexico: An Empirical Analysis

Abstract: This article analyzes the effect of changes in the valued-added tax (VAT) rate on real VAT revenue in Mexico. Recently, there has been a heated debate on the optimal VAT system and the potential economic impact of a reduction in the VAT rate in the country. The results from estimating a VAT revenue model suggest that there seems to be a positive relationship between VAT revenue and the tax rate around the actual VAT rate, contrary to the assertion that there is a Laffer curve for the VAT in Mexico. A 1 percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The results from the variance decompositions (VDC) and impulse response functions (IRF) suggest that VAT rate increases lead to increases in government tax receipts. Thus, the findings support the contention that Mexico is on the upward sloping portion of the Laffer curve (see also Tijerina-Guajardo and Pagán [2000]). Further, VAT revenue falls as a result of a one-time increase in the inflation rate.…”
Section: Income Tax Vatsupporting
confidence: 81%
See 1 more Smart Citation
“…The results from the variance decompositions (VDC) and impulse response functions (IRF) suggest that VAT rate increases lead to increases in government tax receipts. Thus, the findings support the contention that Mexico is on the upward sloping portion of the Laffer curve (see also Tijerina-Guajardo and Pagán [2000]). Further, VAT revenue falls as a result of a one-time increase in the inflation rate.…”
Section: Income Tax Vatsupporting
confidence: 81%
“…As a policy response to the 1994 peso crisis, in April 1995 the Mexican government increased the Value Added Tax (VAT) rate from 10 to 15%. However, recent changes in Mexico's political power structure have led to intense congressional debate on the potential economic effects of a reduction in the VAT rate (Banamex, 1997;Tijerina-Guajardo and Pagán, 2000). Most of this discussion centers on the potential effects of tax law changes on government tax revenue (Banamex, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The International Monetary Fund has carried out a research which deals with a set of key value added tax theoretical provisions, global trends and problems arising from introduction and administration of value added tax (Ebrill, 2001). Tijerina-Guajardo and Pagan (2000) have carried out a research on VAT in Mexico, in which they assessed the impact of various macroeconomic and value added tax regulation factors on income from VAT. Agha and Haughton (1996) have analyzed the impact of a standard VAT tariff on tax avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…It has raised the question, of the impact of other non-standard VAT tariffs on income from VAT. The results have shown that the number of tariffs is statistically important, and a larger number of tariffs increased income from VAT (Tijerina-Guajardo, 2000).…”
mentioning
confidence: 96%
See 1 more Smart Citation